Estratigrafía cuantitativa de las formaciones tablazo y simití en las localidades de sáchica (boyacá) y barichara - san gil (santander), colombia (2002)
This paper will discuss the stratigraphic sections, petrographic and sedimentary environment of Tablazo and Simití formation in sections of Barichara - San Gil (Santander) and Sachica (Boyacá), with a review of the stratigraphic nomenclature. The Tablazo Formation is mainly comprised of shallow deposits marked with bioclastic fragments. Proximal offshore deposits characterize Simiti Formation with sporadic formation influenced by the shallow coastal environment  The variation thickness of cycles (parasecuences) and accumulated thickness of cycles mark the trans-generational behavior of the accommodation space. The cycles generated in Barichara San Gil (Santander) are thirty percent (30%) below average when compared to Sachica (Boyaca).  This concludes that the lirst cycles were deposited in a shallower environment. The basin is shown to have a relative slope of  0.067 degrees lacing south. The curves of Accumulated Deviation of Thickness Average or Fisher diagram shown lor Tablazo and Simiti formations in two sections register transgeneration of the accommodation space. The variation of curves registers tendencies of the successions and can constitute a valuable tool for the delimitation of the lithological segments.  The stratigraphic data from the present study and use of the spectral analysis of Fourier demonstrate cycles measured in the observed units.  Results show a periodicity of fifty meters (50m) in Sachica and twenty-six meters (26m) in Barichara, which can be interpreted as following the orbital parameter of Milankovitch, thus corresponding to its long eccentricity (400ka). Using the orbital indexes, the calculated rate of deposit is 12.7cm/ka in Sachica and 6.5cm/ka in Barichara-San Gil for the Tablazo Formation and Simiti Formation.